Ecological risks and risk mitigation measures related to water quality and agriculture - Lamizana, B.; Drechsel, Pay (2023)
Addressing the ecological impacts of agriculture on water quality, this contribution highlights the urgent need for landscape-based risk mitigation to preserve freshwater ecosystem services. Agricultural practices including monocropping, fertilizer and pesticide use, irrigation drainage, and livestock and aquaculture operations contribute significantly to pollution, biodiversity loss, and downstream eutrophication. The document outlines how nutrient runoff, sedimentation, and chemical contamination from farms disturb aquatic life, reduce oxygen levels, and degrade wetland functions. Emphasizing a precautionary, ecosystem-health approach, the text promotes good agricultural practices tailored to local conditions. These include soil conservation techniques, optimized fertilizer and pesticide use, integrated pest management, and environmentally sound irrigation design. For livestock and aquaculture, waste containment and water treatment measures such as constructed wetlands are recommended. Benchmark indicators like nitrogen and phosphorus thresholds, turbidity, dissolved oxygen, and toxic element concentrations are used to assess ecosystem integrity. The brief also recognizes the importance of behavior change, community awareness, and economic incentives such as certification schemes and payment for ecosystem services (PES) to encourage adoption of sustainable practices. By integrating practical controls with ecological criteria, the guidance offers a roadmap for balancing productivity and environmental resilience in agro-ecosystems.